2019
DOI: 10.2147/ijwh.s213815
|View full text |Cite
|
Sign up to set email alerts
|

<p>The efficacy of intrauterine devices for emergency contraception and beyond: a systematic review update</p>

Abstract: BackgroundThe copper intrauterine device (IUD) is a very effective form of emergency contraception. The failure rate is about 0.1%. IUDs are also very cost-effective when used as long acting-reversible contraception (LARC). The purpose of this review is to attempt to confirm these findings.MethodsThe references for this study were generated by entering the terms “intrauterine device” and “emergency contraception” in Medline, PubMed, Popline, Global Health and ClinicalTrials.gov. Chinese references were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…While there are anecdotal reports of pregnancy with copper IUDs in western countries 80 there are at present no reports of a pregnancy in a single copper IUD for EC study in a western country following two extensive systematic reviews (8,550 insertions and 12 pregnancies, all from Egypt or China). 81,82 Both reviews showed a pregnancy rate of about 0.1%. Only the Multiload IUDs (MLCu 250 and MLCu 375, Multilan SA, Fribourg, Switzerland) and GyneFix (Contrel, Ghent, Belgium) IUDs have an official indication for use as EC.…”
Section: Clinical Evaluation Of the Emergency Copper Iudmentioning
confidence: 99%
“…While there are anecdotal reports of pregnancy with copper IUDs in western countries 80 there are at present no reports of a pregnancy in a single copper IUD for EC study in a western country following two extensive systematic reviews (8,550 insertions and 12 pregnancies, all from Egypt or China). 81,82 Both reviews showed a pregnancy rate of about 0.1%. Only the Multiload IUDs (MLCu 250 and MLCu 375, Multilan SA, Fribourg, Switzerland) and GyneFix (Contrel, Ghent, Belgium) IUDs have an official indication for use as EC.…”
Section: Clinical Evaluation Of the Emergency Copper Iudmentioning
confidence: 99%
“…Los mismos autores en la versión de 2012 y posteriores revisiones sistemáticas, afirman que el DIU de cobre es el método más efectivo (50-52). La tasa de fallo publicada como método de AU es del 0'1% (53). Sin embargo, no es de acceso universal por la falta de infraestructuras ni es la opción más adecuada para mujeres en riesgo de infecciones de transmisión sexual (ITS).…”
Section: Anticoncepción De Emergenciaunclassified
“…Pathway C was specific to Emergency Contraception (EC) copper IUDs and was developed in recognition of the limited use, despite its efficacy. 12 , 13 All pathways guided patients back to the referring GP. The formalized referral pathways aimed to (i) create effective IUD access pathways; (ii) facilitate communication and trust between inserters and the referring GPs; (iii) minimize documentation time by providing referral letter templates and information leaflets for modification as required to be incorporated into GP practice software; and (iv) develop a community of practice to support peer education.…”
Section: Introductionmentioning
confidence: 99%